C / γ-Fe2O3 / TiO2 nanocomposite material and preparation method thereof

By preparing C/γ-Fe2O3/TiO2 nanocomposites with layered and porous structures, the problem of limited photocatalytic activity of pure TiO2 materials under sunlight is solved, and efficient utilization of visible light and effective degradation of pollutants is achieved. .

CN117599789BActive Publication Date: 2024-12-24SHENZHEN TITANIUM & NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311622111.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2024-12-24
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Pure TiO2 materials have limited photocatalytic activity under sunlight and can only absorb ultraviolet light. Photogenerated electrons and holes are prone to recombination, resulting in low efficiency of photocatalytic degradation reactions.

Method used

Using the preparation method of C/γ-Fe2O3/TiO2 nanocomposite material, a two-dimensional carbon sheet with a layered structure and a porous structure are formed by mixing carbonaceous materials, γ-Fe2O3 and titanium dioxide and grinding, calcining and post-treatment. The titanium dioxide nanoparticles in the layered structure, γ-Fe2O3 is loaded on a two-dimensional carbon sheet, improving the visible light utilization rate and charge separation efficiency.

Benefits of technology

It significantly improves photocatalytic activity, enhances the absorption of visible light and the adsorption capacity of pollutants, extends the lifetime of photogenerated electrons and holes, and improves the efficiency of photocatalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117599789B_ABST
    Figure CN117599789B_ABST
Patent Text Reader

Abstract

The invention discloses a C / γ-Fe2O3 / TiO2 nanocomposite material and a preparation method thereof, wherein the steps of the preparation method include: (1) mixing a carbonaceous material, γ-Fe2O3 and titanium dioxide and grinding to obtain a precursor powder; (2) calcining the precursor powder in an inert atmosphere to obtain a crude product; (3) sequentially acid-washing, water-washing and drying the crude product to obtain the C / γ-Fe2O3 / TiO2 nanocomposite material. The C / γ-Fe2O3 / TiO2 nanocomposite material of the invention has a large specific surface area, greatly improves the utilization rate of visible light, has a good adsorption capacity for pollutants, and can effectively separate photogenerated electrons and holes, thereby making the C / γ-Fe2O3 / TiO2 nanocomposite material have significant photocatalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a C / γ-Fe2O3 / TiO2 nanocomposite material and a preparation method thereof. Background Art

[0002] With the continuous advancement of global industrialization, environmental pollution is becoming increasingly serious, and environmental protection and sustainable development are urgent. Photocatalytic technology combines the clean and endless advantages of light energy with the needs of environmental protection to degrade toxic, harmful, and difficult-to-decompose organic matter in industrial wastewater, thus showing broad application prospects and huge economic benefits. Semiconductor-mediated photocatalyst technology has been widely used in sewage treatment, space purification, textile disinfection and sterilization due to its green and efficient performance.

[0003] At present, photocatalyst semiconductor materials include TiO2, SnS2, Bi2O3, ZnO2, V2O5, CeO2 and BiPO4, among which TiO2 is considered to be an environmentally friendly photocatalyst material due to its advantages such as high stability, high activity, non-toxicity and biocompatibility. When the titanium dioxide photocatalyst is irradiated with light equal to or greater than its forbidden width energy, it will produce highly active hole-electron pairs, which undergo redox reactions with substances adsorbed on the catalyst surface to generate the main active substance of the photocatalytic reaction - hydroxyl radicals, which can react with organic pollutants and eventually oxidize these pollutants into carbon dioxide, water or salt without generating new pollutants. However, the bandgap of pure TiO2 material is relatively wide, and electron-hole pairs can only be generated under ultraviolet light excitation. Therefore, pure TiO2 material can only absorb and utilize the ultraviolet light part of sunlight, and there is also the problem of easy recombination of photogenerated electrons and holes, and photocatalytic degradation reactions cannot be effectively carried out under sunlight, so the photocatalytic activity is limited in practical applications.

[0004] Therefore, there is an urgent need for a C / γ-Fe2O3 / TiO2 nanocomposite material and a preparation method thereof to solve the deficiencies of the prior art problems. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, by which a C / γ-Fe2O3 / TiO2 nanocomposite material with significant photocatalytic activity can be prepared.

[0006] Another object of the present invention is to provide a C / γ-Fe2O3 / TiO2 nanocomposite material prepared by the above-mentioned method for preparing the C / γ-Fe2O3 / TiO2 nanocomposite material.

[0007] To achieve the above objectives, the present invention provides a method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0008] (1) mixing a carbonaceous material, γ-Fe2O3 and titanium dioxide (TiO2) and grinding the mixture to obtain a precursor powder; (2) calcining the precursor powder in an inert atmosphere to obtain a crude product;

[0009] (3) The crude product is sequentially subjected to acid washing, water washing and drying treatment to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material.

[0010] Compared with the prior art, the present invention mixes carbonaceous material, γ-Fe2O3 and titanium dioxide and grinds them to obtain a precursor powder, and then calcines and post-treats to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material. The composite material includes a two-dimensional carbon sheet with a layered structure and a porous structure, titanium dioxide nanoparticles embedded in the layered structure, and γ-Fe2O3 loaded on the two-dimensional carbon sheet. The two-dimensional carbon sheet with a layered structure and a porous structure can reduce the band gap of titanium dioxide to make it consistent with the visible light spectrum, thereby improving the utilization rate of visible light, and can also promote the transfer of charge from the TiO2 structure to the oxidation reaction surface to suppress the recombination rate of photoelectrons and holes, and enhance the adsorption of pollutants through π-π stacking. , and the porous structure can further improve the absorption of visible light and the adsorption of organic pollutants; titanium dioxide embedded in the layered structure can effectively prevent titanium dioxide from agglomerating at high temperatures, making titanium dioxide have a larger specific surface area to provide a more active reaction center; a heterogeneous junction is formed at the interface between γ-Fe2O3 and the two-dimensional carbon sheet, which can further promote the separation of photogenerated electrons and holes, so that the C / γ-Fe2O3 / TiO2 nanocomposite material has a larger specific surface area, greatly improves the utilization rate of visible light, has a better adsorption capacity for pollutants, and can effectively separate photogenerated electrons and holes, thereby making the C / γ-Fe2O3 / TiO2 nanocomposite material have significant photocatalytic activity.

[0011] Furthermore, the present invention comprises 20 to 40 parts of carbonaceous material, 5 to 8 parts of γ-Fe2O3 and 50 to 75 parts of TiO2 in parts by mass.

[0012] Furthermore, in the present invention, the carbonaceous material, γ-Fe2O3 and titanium dioxide are mixed and then ground in a ball mill for 6 to 12 hours to obtain a precursor powder.

[0013] Furthermore, the calcination in step (2) of the present invention comprises: heating to 800° C. at a rate of 3 to 10° C. / min, maintaining the temperature for 2 to 4 hours, and then cooling to room temperature at a rate of 10 to 15° C. / min.

[0014] Furthermore, the carbonaceous material of the present invention includes at least one of starch, graphene, carbon nanotubes and carbon dots.

[0015] Furthermore, the carbonaceous material of the present invention is starch, which easily expands to form a mesoporous structure in the early stage of calcination, and then forms a two-dimensional carbon sheet with a layered structure and leaves a porous structure through high-temperature carbonization.

[0016] Furthermore, the present invention includes pickling with a 3.0-5.0 mol / L hot hydrochloric acid solution. Pickling is to remove iron or other metal oxides or salts.

[0017] Furthermore, the drying process of the present invention comprises: drying at 45 to 60° C. for 2 to 30 hours.

[0018] Furthermore, the inert atmosphere of the present invention is at least one of nitrogen (N2), hydrogen (H2), helium (He), and argon (Ar).

[0019] Furthermore, the present invention includes placing the precursor powder in a muffle furnace and calcining it under an inert atmosphere to obtain a crude product.

[0020] To achieve the above objectives, the present invention also provides a C / γ-Fe2O3 / TiO2 nanocomposite material, which is prepared by the above-mentioned method for preparing the C / γ-Fe2O3 / TiO2 nanocomposite material.

[0021] Compared with the prior art, the C / γ-Fe2O3 / TiO2 nanocomposite material of the present invention has a larger specific surface area, greatly improved utilization of visible light, better adsorption capacity for pollutants, and effective separation of photogenerated electrons and holes, thereby making the C / γ-Fe2O3 / TiO2 nanocomposite material have significant photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a transmission electron microscopy image of the C / γ-Fe2O3 / TiO2 nanocomposite material prepared in Example 1. DETAILED DESCRIPTION

[0023] In order to further understand the present invention, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0025] Example 1

[0026] This embodiment provides a method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0027] (1) 20 parts by weight of starch, 5 parts by weight of γ-Fe2O3 and 75 parts of titanium dioxide were mixed and ground in a ball mill for 12 hours to obtain a precursor powder;

[0028] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 800° C. at a rate of 3° C. / min, maintaining the temperature for 2 hours, and then cooling to room temperature at a rate of 10° C. / min;

[0029] (3) The crude product was sequentially acid-washed with a 3 mol / L hot hydrochloric acid solution, washed three times with deionized water, and dried in an oven at 45°C for 8 h to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material.

[0030] The morphology and structure of the C / γ-Fe2O3 / TiO2 nanocomposite material prepared in Example 1 were observed using a transmission electron microscope with a magnification of 1,000,000 times and a diameter of 200 nm. Figure 1 As shown. Figure 1 It can be seen that TiO2 nanoparticles are embedded in the carbon layered structure of the two-dimensional carbon sheet.

[0031] Example 2

[0032] This embodiment provides a method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0033] (1) 30 parts by weight of starch, 6 parts by weight of γ-Fe2O3 and 64 parts of titanium dioxide were mixed and ground in a ball mill for 8 hours to obtain a precursor powder;

[0034] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 800° C. at a rate of 7° C. / min, maintaining the temperature for 3 hours, and then cooling to room temperature at a rate of 13° C. / min;

[0035] (3) The crude product was sequentially acid-washed with a 4 mol / L hot hydrochloric acid solution, washed four times with deionized water, and dried in an oven at 50°C for 8 h to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material.

[0036] Example 3

[0037] This embodiment provides a method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0038] (1) 40 parts by weight of starch, 8 parts by weight of γ-Fe2O3 and 52 parts by weight of titanium dioxide were mixed and ground in a ball mill for 10 hours to obtain a precursor powder;

[0039] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 800° C. at a rate of 10° C. / min, maintaining the temperature for 4 hours, and then cooling to room temperature at a rate of 15° C. / min;

[0040] (3) The crude product was sequentially acid-washed with a 5 mol / L hot hydrochloric acid solution, washed six times with deionized water, and dried in an oven at 60°C for 5 h to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material.

[0041] Example 4

[0042] This embodiment provides a method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0043] (1) 20 parts by weight of starch, 5 parts by weight of γ-Fe2O3 and 75 parts by weight of titanium dioxide were mixed and ground in a ball mill for 12 hours to obtain a precursor powder;

[0044] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 800° C. at a rate of 3° C. / min, maintaining the temperature for 1.5 h, and then cooling to room temperature at a rate of 10° C. / min;

[0045] (3) The crude product was sequentially acid-washed with a 3 mol / L hot hydrochloric acid solution, washed three times with deionized water, and dried in an oven at 45°C for 8 h to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material.

[0046] Example 5

[0047] This embodiment provides a method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0048] (1) 20 parts by weight of starch, 5 parts by weight of γ-Fe2O3 and 75 parts by weight of titanium dioxide were mixed and ground in a ball mill for 12 hours to obtain a precursor powder;

[0049] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 700° C. at a rate of 3° C. / min, maintaining the temperature for 2 h, and then cooling to room temperature at a rate of 10° C. / min;

[0050] (3) The crude product was sequentially acid-washed with a 3 mol / L hot hydrochloric acid solution, washed three times with deionized water, and dried in an oven at 45°C for 8 h to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material.

[0051] Comparative Example 1

[0052] This comparative example provides a method for preparing a C / TiO2 nanocomposite material, the steps comprising:

[0053] (1) 20 parts by weight of starch and 75 parts by weight of titanium dioxide were mixed and ground in a ball mill for 12 hours to obtain a precursor powder;

[0054] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 800° C. at a rate of 3° C. / min, maintaining the temperature for 2 hours, and then cooling to room temperature at a rate of 10° C. / min;

[0055] (3) The crude product was sequentially acid-washed with a 3 mol / L hot hydrochloric acid solution, washed three times with deionized water, and dried in an oven at 45°C for 8 h to obtain a C / TiO2 nanocomposite material.

[0056] Comparative Example 2

[0057] This comparative example provides a method for preparing a γ-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0058] (1) 5 parts by mass of γ-Fe2O3 and 75 parts by mass of titanium dioxide were mixed and ground in a ball mill for 12 hours to obtain a precursor powder;

[0059] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 800° C. at a rate of 3° C. / min, maintaining the temperature for 2 hours, and then cooling to room temperature at a rate of 10° C. / min;

[0060] (3) The crude product was sequentially acid-washed with a 3 mol / L hot hydrochloric acid solution, washed three times with deionized water, and dried in an oven at 45°C for 8 h to obtain a γ-Fe2O3 / TiO2 nanocomposite material.

[0061] Comparative Example 3

[0062] This comparative example provides a method for preparing a C / α-Fe2O3 / TiO2 nanocomposite material, the steps comprising:

[0063] (1) 20 parts by weight of starch, 5 parts by weight of α-Fe2O3 and 75 parts by weight of titanium dioxide were mixed and ground in a ball mill for 12 hours to obtain a precursor powder;

[0064] (2) placing the precursor powder in a muffle furnace and calcining it in a nitrogen inert atmosphere to obtain a crude product, wherein the calcination comprises: heating to 800° C. at a rate of 3° C. / min, maintaining the temperature for 2 hours, and then cooling to room temperature at a rate of 10° C. / min;

[0065] (3) The crude product was sequentially acid-washed with a 3 mol / L hot hydrochloric acid solution, washed three times with deionized water, and dried in an oven at 45°C for 8 h to obtain a C / α-Fe2O3 / TiO2 nanocomposite material.

[0066] The nanocomposites prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to photocatalytic experiments in a heat-resistant reactor at room temperature according to the following test method. The photocatalytic activity was evaluated by the degradation of pink rhodamine B under visible light irradiation. The test results are shown in Table 1.

[0067] Photocatalytic experiment: 10 mg of nanocomposite was added to 50 mL of 10 mol / L rhodamine B aqueous solution and magnetically stirred in the dark for 0.5 h to establish absorption-desorption equilibrium before turning on the light. Samples were collected using a syringe at preselected time intervals and filtered through a 0.45 μm polytetrafluoroethylene (PTFE) syringe filter to remove particles. The concentration of rhodamine B was quantitatively determined by high performance liquid chromatography (HPLC, Shimadzu LC-20A).

[0068] Table 1 Degradation rate of Rhodamine B

[0069] Group After 60min, the degradation rate Example 1 96% Example 2 97% Example 3 96.5% Example 4 93% Example 5 94% Comparative Example 1 81.2% Comparative Example 2 60% Comparative Example 3 72.3%

[0070] Specifically, the photocatalytic principle of C / γ-Fe2O3 / TiO2 nanocomposites is as follows: when C / γ-Fe2O3 / TiO2 nanocomposites are irradiated with visible light, photogenerated electrons are excited to migrate from the valence band (VB) to the conduction band (CB), and due to the close coupling of titanium dioxide nanoparticles, they migrate to the carbon layer, resulting in the effective separation of electrons and holes. The separated electrons can react with the adsorbed O2 to form O2 - , photo-oxidation of pollutants, and at the same time, the remaining holes in titanium dioxide can also participate in the redox reaction by forming OH radicals. Therefore, the electrons and holes generated by light are effectively separated, and the lifetime of the excited electrons and holes can be extended during the transfer process.

[0071] As shown in Table 1, after 60 minutes, the degradation rates of Rhodamine B in all embodiments are more than 93%. This is because in the present invention, the carbonaceous material, γ-Fe2O3 and titanium dioxide are mixed and ground to obtain a precursor powder, and then calcined and post-treated to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material, which includes a two-dimensional carbon sheet with a layered structure and a porous structure, titanium dioxide nanoparticles embedded in the layered structure, and γ-Fe2O3 loaded on the two-dimensional carbon sheet, wherein the two-dimensional carbon sheet with a layered structure and a porous structure can reduce the band gap of titanium dioxide to make it consistent with the visible light spectrum, thereby improving the utilization rate of visible light, and can also promote the transfer of charge from the TiO2 structure to the oxidation reaction surface to suppress the recombination rate of photoelectrons and holes, and enhance the adsorption of pollutants through π-π stacking. The porous structure can further improve the absorption of visible light and the adsorption of organic pollutants; titanium dioxide embedded in the layered structure can effectively prevent titanium dioxide from agglomerating at high temperatures, so that titanium dioxide has a larger specific surface area to provide a more active reaction center; a heterogeneous junction is formed at the interface between γ-Fe2O3 and the two-dimensional carbon sheet, which can further promote the separation of photogenerated electrons and holes. In this way, the C / γ-Fe2O3 / TiO2 nanocomposite material has a larger specific surface area, greatly improves the utilization rate of visible light, has a better adsorption capacity for pollutants, and can effectively separate photogenerated electrons and holes, thereby making the C / γ-Fe2O3 / TiO2 nanocomposite material have good dispersibility and high stability, which can provide a unique nanoscale reaction space for photocatalytic reactions and improve reaction efficiency.

[0072] By comparing Example 1 with Examples 4 to 5, it can be seen that the degradation rate of Rhodamine B after being treated with the nanocomposite material of Example 1 for 60 minutes is slightly better than that of Examples 4 to 5, which indicates that the calcination temperature and time will affect the morphology and structure of the C / γ-Fe2O3 / TiO2 nanocomposite material and thus affect the catalytic performance, that is, the calcination of the present invention is preferably: heating to 800°C at a rate of 3 to 10°C / min, maintaining the temperature for 2 to 4 hours, and then cooling to room temperature at a rate of 10 to 15°C / min.

[0073] Comparing Example 1 with Comparative Example 1, the degradation rate of Rhodamine B in Comparative Example 1 is lower than that in Example 1. This is because γ-Fe2O3 is loaded on the two-dimensional carbon sheet in Example 1, and a heterogeneous junction is formed at the interface between γ-Fe2O3 and the two-dimensional carbon sheet, which can promote the separation of photogenerated electrons and holes. Therefore, removing γ-Fe2O3 will affect the photocatalytic performance of the composite material.

[0074] Comparing Example 1 with Comparative Example 2, the degradation rate of Rhodamine B in Comparative Example 2 is lower than that in Example 1. This is because the composite material of Example 1 has a two-dimensional carbon sheet with a layered structure and a porous structure, and titanium oxide is combined with the two-dimensional carbon sheet to obtain a higher specific surface area, effectively inhibit the recombination rate of photoinduced electron-hole pairs, and improve the utilization rate of visible light and the adsorption capacity of pollutants, thereby generating more active photocatalytic substances to improve the photocatalytic performance. Therefore, removing starch will affect the photocatalytic performance of the composite material.

[0075] By comparing Example 1 with Comparative Example 3, it was found that the degradation rate of Rhodamine B in Comparative Example 3 was lower than that in Example 1, which indicates that after adjusting γ-Fe2O3 to α-Fe2O3, a heterogeneous junction that can promote the separation of photogenerated electrons and holes cannot be formed at the interface between α-Fe2O3 and the two-dimensional carbon sheet, thereby affecting the photocatalytic performance.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a C / γ-Fe2O3 / TiO2 nanocomposite material, characterized in that the steps include: (1) Starch, γ-Fe2O3 and titanium dioxide are mixed and ground to obtain a precursor powder; (2) calcining the precursor powder in an inert atmosphere to obtain a crude product; (3) sequentially subjecting the crude product to acid washing, water washing, and drying treatments to obtain a C / γ-Fe2O3 / TiO2 nanocomposite material; In terms of mass, it includes 20 to 40 parts of starch, 5 to 8 parts of γ-Fe2O3 and 50 to 75 parts of TiO2; The calcination in step (2) includes: heating to 800°C at a rate of 3-10°C / min, maintaining the temperature for 2-4 hours, and then cooling to room temperature at a rate of 10-15°C / min.

2. The method for preparing the C / γ-Fe2O3 / TiO2 nanocomposite material according to claim 1, characterized in that: The method comprises using a 3.0-5.0 mol / L hot hydrochloric acid solution for pickling.

3. The method for preparing the C / γ-Fe2O3 / TiO2 nanocomposite material according to claim 1, characterized in that: The drying treatment comprises: drying at 45-60° C. for 2-30 hours.

4. The method for preparing the C / γ-Fe2O3 / TiO2 nanocomposite material according to claim 1, characterized in that: The inert atmosphere is at least one of N2, He, and Ar.

5. The method for preparing the C / γ-Fe2O3 / TiO2 nanocomposite material according to claim 1, characterized in that: The method comprises placing the precursor powder in a muffle furnace and calcining the precursor powder under an inert atmosphere to obtain a crude product.

6. A C / γ-Fe2O3 / TiO2 nanocomposite material, characterized in that: The material is prepared by the method for preparing the C / γ-Fe2O3 / TiO2 nanocomposite material as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Ternary composite photocatalytic material, preparation method thereof, and method for degrading PPCPs in water

    CN113559908A